The Effectiveness of Application of the Confins System in Consumer Service at BFI Gorontalo - Srihandayani Suprapto; Bunga Ratna Deu (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The research was conducted at BFI Finance of Gorontalo. The type of research was descriptive. Technique collecting data used observation, interview, and documentation. Technique of analysis data used descriptive qualitative. The research aims to examine the application of Confins System at BFI Finance of Gorontalo. The result show that a multi-finance company as a whole from the determination process to control payments to vehicle owners must be appropriate, because ERP Confins which have an operational reporting application, which is useful for producing reports in various forms tailored to the needs of the company, have not been effective in accordance with standards BFI Finance work. BFI Finance of Gorontalo experiences obstacles in terms of content, as well as in the format of the report with the suitability of the vehicle owner, in this case the consumer is different from the name listed in the Certificate of Ownership of Motor Vehicles (BPKB), thus hampering the effectiveness of the running of the compony. Human resources are also an important reason for BFI Finance of Gorontalo for company development that is not only seen from a physical, mental and moral point of view, but from a work productivity perspective.